Improvement of Erdheim-Chester disease-related renal failure after treatment with anakinra - Manuel Alfredo Podestà; Giorgio Graziani; Francesco Reggiani; Michele Buemi; Salvatore Badalamenti; Claudio Ponticelli (The Korean Society of Nephrology, 2014)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis characterized by infiltrates of lipid-laden CD68+/CD1a− histiocytes, affecting heart, lungs, central nervous system, and bones. Kidney and adjacent structures can also be affected, leading to renal failure in about 30% of cases. The diagnosis is challenging, and treatment is generally based on administration of interferon-alpha (IFNα), but preliminary results also showed the therapeutic efficacy of anakinra, an antagonist of the receptor of interleukin-1 (IL-1). We report the case of an elderly patient with ECD and severe involvement of the heart and kidneys who was successfully treated with anakinra.